[PP.19.21] ASSOCIATION BETWEEN QTC AND VASCULAR STIFFNESS. (September 2017) - Di Leva, A.; Boscaro, M.; Botto, F.; Obregon, S.; Bang, J.; Koretzky, M.; Sohn, G. Fischer; Kotliar, C.
Abstract : Objective: QTc prolongation is associated with hypertension, insulin resistance, body mass index increase (BMI), left ventricular hypertrophy, female gender, and subclinical artheriosclerosis. Among hypertensives an increased arterial stiffness is considered as a subclinical target organ damage. Our hypothesis was that a direct association between QT interval duration and arterial stiffness could be identified suggesting their interaction towards a higher cardiovascular risk. Aims (a) To evaluate the distribution of corrected QTc duration in hypertensive patients (HP) in comparison with a control group and (b) to determine the association between QTc and vascular stiffness in the general population. Figure. No caption available. Design and method: The study included 53 patients considered as general population, and then classified as hypertensive (n: 30), and normotensive (n:23), age: 55, 13 +/− 9, 94 years, male: 34, female:19. Arterial pressure, vascular stiffness, index of left ventricular mass (LVMI) and QTc interval were measured. Patients were divided in tertiles according to the QTc duration: T1 QTc 350–400 msec, T2 QTc 400–439 msec and T3 QTc > 440 msec. Results: No major differences was observed between the hypertensive patients group and the control group in terms of age (p 0, 0873), gender (p 0, 6142), diabetes (p 0, 8721), sedentary lifestyle (p 0, 0650), and smoking (p 0, 9121). Difference was observed in systolic blood pressure (SBP), p 0, 00365, diastolic blood pressure (DBP) p 0, 001 and QTc (406, 10 +/− 29, 6 versus 391, 76 +/− 21, 1 p 0, 0345). Table 1 The QTc correlated in univariate form with PWV (p 0, 0050) and with SBP (p 0, 0328). When making a multivariate analysis the association between PWV and QTc remained unchanged (p 0, 0232). The AUC was 0, 686 (p 0.0154), with a 83, 3% sensitivity, 58.54% specificity and a cut point of 402 mseg for QTc as predictor of vascular stiffness increase. Conclusions: The QTc values were more prolonged in hypertensive patients. Furthermore, a direct association between QTc length and arterial stiffness was observed.